ALMA (finally!) discloses a rotating disk+bipolar wind system at the centre of the wind-prominent pPN OH 231.8+4.2. Issue Volume 16:Issue S366(2020) (November 2020) - Sánchez Contreras, C.; Alcolea, J.; Rodríguez-Cardoso, R.; Bujarrabal, V.; Castro-Carrizo, A.; Velilla-Prieto, L.; Quintana-Lacaci, G.; Santander-García, M.; Agúndez, M.; Cernicharo, J.
Abstract: We present interferometric continuum and molecular line emission maps obtained with the Atacama Large Millimeter/submillimeter Array (ALMA) of OH231.8+4.2, a well studied bipolar nebula around an asymptotic giant branch (AGB) star that is key to understand the remarkable changes in nebular morphology and kinematics during the short transition from the AGB to the Planetary Nebula (PN) phase. The excellent angular resolution of our maps (∼20 mas ∼30 AU) allows us to scrutinize the central nebular regions of OH231.8+4.2, which hold the clues to understanding how this iconic object assembled its complex nebular architecture. We report, for the first time in this object and others of its kind (i.e. pre-PNe with massive bipolar outflows), the discovery of a rotating circumbinary disk of radius ∼30 AU traced by NaCl, KCl, and H2 O emission lines. The disk lies at the base of a young bipolar wind with signs of rotation as well. A compact spatially resolved dust disk is found perpendicular to the bipolar outflow. We also identify a point-like continuum source, which likely represents the central Mira star enshrouded by a ∼3 R * shell or disk of hot (∼1400 K) freshly formed dust. The point source is slightly off-centre from the disk centroid, enabling us for the first time to place constraints to the orbital separation of the central binary system.